2007
DOI: 10.1097/iop.0b013e3181462a2e
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic Receptors in the Ptotic Human Eyelid: Correlation With Phenylephrine Testing and Surgical Success in Ptosis Repair

Abstract: Alpha 1D, alpha-2C, and beta-2 receptors are documented within human Müller muscle. Human eyelid elevation response to phenylephrine is inversely related to the amount of alpha-2C receptor staining in Müller muscle. Fasanella and Putterman procedures have equal outcomes, independent of adrenergic receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 14 publications
3
21
0
Order By: Relevance
“…These behavioral changes presumably are mediated by the blocking of histamine H 1 receptor or ␣ 1 receptor (Skibell et al, 2007), and these results are in agreement with in vitro receptor binding profiles that lurasidone has relatively low affinity for noradrenergic ␣ 1 receptor or negligible affinity for histamine H 1 receptor. These findings suggested that lurasidone would have fewer risks of cardiovascular side effects, such as orthostatic hypotension, and CNS depressant side effects, such as sedation or somnolence.…”
Section: Discussionsupporting
confidence: 74%
“…These behavioral changes presumably are mediated by the blocking of histamine H 1 receptor or ␣ 1 receptor (Skibell et al, 2007), and these results are in agreement with in vitro receptor binding profiles that lurasidone has relatively low affinity for noradrenergic ␣ 1 receptor or negligible affinity for histamine H 1 receptor. These findings suggested that lurasidone would have fewer risks of cardiovascular side effects, such as orthostatic hypotension, and CNS depressant side effects, such as sedation or somnolence.…”
Section: Discussionsupporting
confidence: 74%
“…20 However, eyelid elevation response to phenylephrine was not correlated with the amount of the receptors, consistent with this study. The authors found that the effect of phenylephrine was inversely related to the amount of α 2C -adrenoceptor staining.…”
Section: Discussionsupporting
confidence: 82%
“…Revision of the literature on etiologies responsible for the signs present in the Horner's syndrome revealed a number of diseases specifically associated with Horner's syndrome, such as Pancoast tumor of the lung (Attar et al 1998), Rowlend-Payne syndrome, caused by mediastinal neuroblastoma (Kapoor et al 2005), pseudoaneurysm of the internal carotid artery (Mastan 2005), metastatic breast cancer (Kovacic et al 2007), some congenital lesions (Castillo et al 2005;Gupta et al 2005) and metastatic tumor of the cavernous sinus (Tsuda et al 2005). Sympathetic fibers with adrenergic receptors alpha-1D, alpha-2C and beta-2 receptors have been documented within human STM, and the alpha-2C receptor in particular may play a role in determining the response of the eyelid to phenylephrine (Skibell et al 2007).…”
Section: Discussionmentioning
confidence: 99%